Potential role of Manilkara Zapota L in treating bacterial infection - Ami Febriza; Fityatun Usman; Andi Ulfah Magefirah Rasyid; Hasta Handayani Idrus; Mohd Helmy Mokhtar (PeerJ, 2024)
The increasing problem of antibiotic resistance in bacteria leads to an urgent need for new antimicrobial agents. Alternative treatments for bacterial infections need to be explored to tackle this issue. Plant-based substances are emerging as promising options. Manilkara zapota L. contains compounds with antibiotic activities, and anti-inflammatory, antitumor, antipyretic, and antioxidant properties. It has medicinal properties and contains bioactive compounds, like tannins, flavonoids, and triterpenoids. This review aimed to comprehensively evaluate the existing literature on the potential medicinal and therapeutic benefits of M. zapota in bacterial infections by utilizing data from in vivo and in vitro studies. M. zapota has the potential to be a nutritional source of antimicrobial food. Numerous preclinical studies have demonstrated the antibacterial activities of M. zapota and its components. The antibacterial mechanisms of this fruit could interact with bacterial cell structures such as cell walls or membranes.